Multiple sclerosis: major histocompatibility complexity and antigen presentation - Ramagopalan, Sreeram V (BioMed Central, 2009)
Multiple sclerosis (MS), like many putative autoimmune diseases, has been known to be associated with the human leukocyte antigen (HLA) class II region for more than 3 decades. However, exactly how HLA class II alleles increase the risk of MS is not yet conclusively known. Recent work in large human cohorts has highlighted the fact that nearly all common HLA-DRB1 allelotypes are either positively or negatively associated with the disease, detracting from allele-specific antigen presentation as the sole mechanism of MHC associated disease susceptibility. Here, we put into context recent data on the HLA class II region in MS, including allelic heterogeneity, gene-environment interactions and epigenetics. It is clear that a complete understanding of the epistatic interactions and epigenetic features of this region will be crucial to comprehending disease pathogenesis.